A SYSTEMATIC LITERATURE REVIEW ON THE FISHERMEN’S KNOWLEDGE OF INTEGRATING FISHING AND TOURISM ACTIVITIES - Roslan, Faros Fadzira; Zainol, Rosilawati; Rosni, Nur Aulia (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
Education for the future requires everyone to consider the pillars of sustainability in carrying out their daily activities. It is crucial to note that education is an essential ingredient in achieving sustainable development. Fishermen, for example, live in poverty due to a lack of proper knowledge and learning exposure. Having greater insight into this research area would yield helpful information about the impact of education on the fishermen’s community’s well-being. The integration of fishing and tourism disciplines is ongoing and has produced positive results. An in-depth examination at how fishing and tourism might work together is presented here for the first time. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) publication standard has been employed as a key research design approach. Web of Science and Scopus are the two key databases used in this study. A total of eleven (11) articles are eligible for review and analysis. Three (3) themes emerged from the thematic analysis, namely, 1) fishing and tourism, 2) knowledge, and 3) rural economies. This study proposes two (2) recommendations. To begin, there is a dire need for additional qualitative research because it is the only method to deliver comprehensive and precise knowledge. Second, authors can report reviews on any study in a systematic manner when they use the PRISMA method.